2008
DOI: 10.1109/tevc.2007.906095
|View full text |Cite
|
Sign up to set email alerts
|

Protein Folding in Simplified Models With Estimation of Distribution Algorithms

Abstract: Abstract-Simplified lattice models have played an important role in protein structure prediction and protein folding problems. These models can be useful for an initial approximation of the protein structure, and for the investigation of the dynamics that govern the protein folding process. Estimation of distribution algorithms (EDAs) are efficient evolutionary algorithms that can learn and exploit the search space regularities in the form of probabilistic dependencies. This paper introduces the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 78 publications
0
73
0
3
Order By: Relevance
“…Many works in the literature confirm the good performance of EDAs in the solution of problems from diverse fields. Protein Folding [45], Capacitated Vehicle Routing Problems [52], Calibration of Chemical Applications [35], Finding the Optimal Path in 3D Spaces [53], Software Testing [44], Chemotherapy Treatment Optimization for Cancer [6] or Nuclear Reactor Fuel Management Parameter Optimization [21] are some examples of many real-world problems where EDA-based approaches were applied to find optimal solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Many works in the literature confirm the good performance of EDAs in the solution of problems from diverse fields. Protein Folding [45], Capacitated Vehicle Routing Problems [52], Calibration of Chemical Applications [35], Finding the Optimal Path in 3D Spaces [53], Software Testing [44], Chemotherapy Treatment Optimization for Cancer [6] or Nuclear Reactor Fuel Management Parameter Optimization [21] are some examples of many real-world problems where EDA-based approaches were applied to find optimal solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Implementação de técnicas de busca local, cujo impacto positivo tem sido demonstrado em trabalhos relacionados (Krasnogor, 2002;Bazzoli and Tettamanzi, 2004); 4. Pesquisa do impacto de técnicas de aumento de desempenho de AEs desenvolvidas recentemente, como os chamados algoritmos de estimação de distribuição (Santana et al, 2008;Melo, 2009). …”
Section: Conclusõesunclassified
“…In Santana et al (2008b), it was shown that EDAs can achieve state-of-the-art results in the optimization of the HP protein model. Here we show how Mateda-2.0 can be used to implement an EDA approach to this problem.…”
Section: Fda Optimization Of the Hp Protein Modelmentioning
confidence: 99%
“…Figure 1 shows one of the optimal solutions found by this algorithm in generation 144. This solution is very hard to find for state-of-the-art algorithms (Santana et al 2008b). Figure 2 illustrates the steady increase in the average fitness of the solutions with the generations.…”
Section: Fda Optimization Of the Hp Protein Modelmentioning
confidence: 99%